Risk Assessment in Cement Industry - A Multi-Criterial Decision for Selecting the Appropriate Risks Assessment Methods - Constantin Cristian DEOPALE; Liviu Daniel GHICULESCU (Communications of International Proceedings, 2021)
Operating in a changing market economy and under increasing pressure especially due to the necessity of reducing emissions of greenhouse-effect gas in the atmosphere, organizations from the cement industry must permanently assess their risks in order to know, the threats they will face to. The high number of risk assessment methods developed in the last years, each of them with strengths and limitations, means that the decision of choosing the adequate instrument to achieve the assessment goal is a rather difficult one. The goal of this paper is to propose a solution to this challenge, therefore the first part of this paper focuses on performing a literature review regarding the risk assessment methods used in the cement industry, by using a set of structured elements based on the PRISMA method. In the next step, we propose 20 criteria that must be at the basis of the decisional process regarding the selection of the risk assessment methods, considering the specificity of the cement industry. In the final part of the research, we performed an analysis of the risk assessment methods based on the proposed decision criteria, which allowed us to estimate their global utility level for cement industry. This research can be a useful instrument for specialists and risk managers form cement industry during the decisional process related to the selection of risk assessment methods.
Keywords: Risk Management; Risk Assessment Methods; Cement Industry; Management Systems.